2019
DOI: 10.1111/jcmm.14600
|View full text |Cite
|
Sign up to set email alerts
|

Hoxa5 alleviates obesity‐induced chronic inflammation by reducing ER stress and promoting M2 macrophage polarization in mouse adipose tissue

Abstract: Obesity‐induced chronic inflammation is associated with endoplasmic reticulum stress (ERS) in adipocytes and changes in both the number and phenotype of adipose tissue macrophages (ATMs). In addition, ERS enhances macrophage activation. So far, the function of Hoxa5 in obesity‐induced chronic inflammation has been poorly understood. Herein, we demonstrate the importance of the transcription factor, Hoxa5, in determining adipose tissue macrophage (ATM) polarity and ERS. Hoxa5 decreased bodyweight, reduced infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…Expression of all 3 genes was elevated in AT of DKO-HFD mice. In gonadal and subcutaneous AT, expression of several beige/brown fat markers [ 31 , 58 ] including Slc29a1 and Hoxa5 [ 59 ], was increased in DKO mice, even on the CD, consistent with the other changes in gene expression that we observed.…”
Section: Discussionsupporting
confidence: 86%
“…Expression of all 3 genes was elevated in AT of DKO-HFD mice. In gonadal and subcutaneous AT, expression of several beige/brown fat markers [ 31 , 58 ] including Slc29a1 and Hoxa5 [ 59 ], was increased in DKO mice, even on the CD, consistent with the other changes in gene expression that we observed.…”
Section: Discussionsupporting
confidence: 86%
“…A variety of immunocytes are involved in inflammation ( Mack, 2018 ; Tsai et al, 2018 ). Acute inflammation is dominated by neutrophil infiltration ( Pinho-Ribeiro et al, 2018 ; Kapur et al, 2019 ), whereas chronic inflammation is often accompanied by macrophage and lymphocyte infiltration ( Cao et al, 2019 ; Faissner et al, 2019 ; Lodygin et al, 2019 ; Na et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…, whereas chronic inflammation is often accompanied by macrophage and lymphocyte infiltration (Cao et al, 2019;Faissner et al, 2019;Lodygin et al, 2019;Na et al, 2019).…”
mentioning
confidence: 99%
“…However, the effect of LIPUS on P-PDLSCs was unclear, which has limited the application of LIPUS in the treatment of periodontitis, because the inflammatory environment is unavoidable during periodontitis treatment. A study by Cao et al has shown that suppression of ERS could alleviate chronic inflammation in adipocytes [31]. As a molecular chaperone, 4-PBA reduced excessive ER load caused by mutations or mislocated proteins in the study of liver injury [32] and could inhibit ERS-mediated apoptosis and prevent cerebral ischemia [33].…”
Section: Discussionmentioning
confidence: 99%